Anti-obesity activities of edible bird nest on 3T3-L1 adipocytes and high fat-cholesterol diet induced-obese rabbits - Mohamad Ibrahim, Ramlah (2022)
Obesity has become a global public health issue with increasing prevalence in the recent decade. Managing obesity with anti-obesity drugs have been marked by numerous adverse effects. Therefore, current research focuses on commonly consumed foods to provide multi-target functions beyond their traditional nutritive values which would likely prevent obesity. Edible bird nest (EBN) is made from saliva of swiftlets which was deemed as an important ethno-medicinal commodity for its nutritional and healing values. Growing evidence suggests EBN as a potential functional food for managing metabolic disorders, which has initiated the present study to explore the therapeutic benefit of EBN to prevent obesity and its related disorders. The present study evaluated the comparative analysis in nutrient compositions between two different shapes of housefarmed EBN which are half cup and stripe-shape EBN. Nutrient analysis showed half cup EBN has significantly higher protein, carbohydrate, calcium and sulfur content compared to stripe-shaped EBN (p < 0.05). Next, stew extract (SE) and full stew (FS) was prepared form half cup EBN to determine sialic acid (SA) content and subsequently evaluated for their antioxidant effects and enzyme inhibition activities. Stew extract exhibited higher SA content than FS and both EBN showed significantly greater antioxidant and enzyme inhibition activities at concentration of 10 mg/mL (p < 0.05). In vitro anti-adipogenic potential of SA standard (1 mg/mL), SE and FS (10 mg/mL) on 3T3-L1 adipocytes showed significant reduction in lipid accumulation, lipase and G3PDH enzymes level (p < 0.05). The anti-obesity effect of EBN were further evaluated in high fat-cholesterol diet (HFCD)-induced obese rabbits for 12 weeks. Both SE and FS groups significantly prevented weight gain and improved Lee Index as well as reduced white adipose tissue and liver weights compared to HFCD group (p < 0.05). Also, the EBN groups significantly improved serum lipid profile, free fatty acids, leptin, adiponectin, IL-6, MCP-1 and catalase levels (p < 0.05). Gene expression studies revealed that the anti-obesity effects of EBN were associated to regulation of adipokines and adipogenesis along with AMPK activation which significantly improved genes involved in lipid metabolism pathway. Furthermore, SE and FS significantly inhibit NF- κB signalling pathway which in turn downregulated the expression of pro-inflammatory (IL-6, CRP, MCP-1) and insulin resistance (IRS1) genes. Supplementation of SE and FS significantly enhanced the expression of antioxidant genes such as SOD3, CAT, GSR and PON1 (p < 0.05). Additionally, both SE and FS supplementation prevented the toxicity effect of HFCD reflected with significant reduction of ALT and GGT enzymes level (p < 0.05). In conclusion, the present study indicates that EBN via synergism of SA and other nutrients provide anti-obesity action through regulation of genes involved in adipokines, adipogenesis, lipid metabolism along with improvement in obesity-mediated inflammation, insulin resistance and antioxidants.